2015
DOI: 10.3945/jn.115.212092
|View full text |Cite
|
Sign up to set email alerts
|

Consuming High-Protein Soy Snacks Affects Appetite Control, Satiety, and Diet Quality in Young People and Influences Select Aspects of Mood and Cognition

Abstract: Afternoon snacking, particularly on HP soy foods, improves appetite, satiety, and diet quality in adolescents, while beneficially influencing aspects of mood and cognition. This trial was registered at clinicaltrials.gov as NCT01781286.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…Some previous studies have investigated the impact of animal vs. plant-based HP diets on weight loss, appetite and ingestive behaviour, and cardiovascular disease risk factors (7)(8)(9)(10). In general, findings from these studies support a broadly beneficial impact of HP diets with limited differences between animal-based and plant-based diets (7).…”
Section: Introductionmentioning
confidence: 84%
“…Some previous studies have investigated the impact of animal vs. plant-based HP diets on weight loss, appetite and ingestive behaviour, and cardiovascular disease risk factors (7)(8)(9)(10). In general, findings from these studies support a broadly beneficial impact of HP diets with limited differences between animal-based and plant-based diets (7).…”
Section: Introductionmentioning
confidence: 84%
“…The effects of acute chia seed consumption on POMS scores were explored in the current study to determine whether or not chia seed supplementation exerts any undesirable sense or mood state. The link between these parameters originated from a different study, which reported that ingestion of snacks with different nutritional compositions is associated with better mood aspects [ 46 ]. Chia seed consumption did not alter mood states in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, muffins made with soy flour elicited greater feeling of fullness scores among mildly hypercholesterolemic overweight adults, compared to a wheat muffin supplemented with whey protein [156]. In another study, snacks made with soy protein isolates led to greater reductions in appetite and reduced intake of sugary snacks in the evening among adolescents [157], and a breakfast high in soy protein reduced serum appetite hormones including ghrelin and protein YY [158]. Obese mice also exhibited greater satiety while consuming whey protein as compared to soy protein [159].…”
Section: Contribution Of Soy Based Foods To Satietymentioning
confidence: 99%